Influence of Microwave Radiation on Growth of Calcium Sulphate Crystal by Monte Carlo Method - YANG*, XIAO-QING; YANG, LI-JUN; HUANG, KA-MA (Asian Journal of Chemistry, 2009)
Microwaves are widely used in synthesis of biomaterials. Many experiments show that the crystal shape of biomaterials with microwave synthesis is quite different from the one with conventional method under the same crystal conditions. In this paper, we analyze the influence of microwave radiation on calcium sulphate crystal growth by Monte Carlo method and explain the reason for difference of shape. The results show microwave can deduce the surface tension and viscosity so as to influence the crystal growth and shape.